Finding a middle ground: Conservation challenges among stakeholders in coastal Tanzania (Respond to this article at http://www.therai.org.uk/at/debate). Issue 1 (February 2014) - Naar, Nicole; Mahenge, Jairos
<x xml:space="preserve">Abstract</x> Recently, evictions associated with climate change mitigation in the Rufiji Delta of Tanzania sparked intense debate about the ethics of coastal conservation between academics, NGOs (non‐governmental organizations) and government officials working in the region. Some actors argue that environmental change is a myth used to wrest control of natural resources from local communities, while others point to the urgency of environmental protection and action on climate change. Insights gleaned from interviews with multiple government officials, NGO employees, academics, and coastal village residents in Pangani, however, reveal a more complex and perhaps less contentious situation in coastal Tanzania. Although they often proffered different solutions, different stakeholder groups articulated the same key challenges in nuanced ways that shed a more hopeful light on currently heated conservation and development issues.